Ordinances of the Borough of Vincennes, with the Act of Incorporation and Supplement Thereto Prefixed 54-55 (1820) - (:unkn) unknown (My University, 1819)
Prohibited "any negro or mulatto" from possessing "deadly weapons."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES